Body image, sexual activity, and side effects of treatments across the first year after surgery in women facing breast cancer: The influence of attachment insecurity. Issue 6 (2nd November 2021) - Favez, Nicolas; Cairo Notari, Sarah
Abstract: Objectives: The aim of this study was to assess, across the first year after surgery, the influence of attachment insecurity, that is, avoidant and anxious tendencies, on body image, sexual activity, and side effects of treatments in women diagnosed with breast cancer. Design: A total of 110 women with non-metastatic breast cancer were surveyed 2 weeks (T1), 3 months (T2), and 12 months (T3) after surgery. Methods: Self-reported questionnaires were used to assess attachment tendencies (avoidance and anxiety), medical data (cancer stage, oncological treatment), sociodemographic data (age, socioeconomic level, relational status), and the three outcomes. Results: Generalized linear modeling showed that (1) having more avoidant and anxious attachment tendencies predicted a more negative body image, as did being younger and having undergone a mastectomy; (2) having more avoidant attachment tendencies predicted being sexually inactive, as did having undergone neoadjuvant chemotherapy or adjuvant hormonal therapy, whereas being younger and in a committed relationship predicted being sexually active; and (3) attachment tendencies did not predict the intensity of side effects, whereas a higher cancer stage and being at the beginning of treatment predicted more side effects. Conclusions: Women with avoidant and anxious attachment tendencies may be especially vulnerable to the consequences of oncological treatment, in particular regarding body image and sexual activity.